2006
DOI: 10.1002/hipo.20198
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of gene expression in the left and right hippocampal formation of developing rats

Abstract: A central problem in neurobiology is the elucidation of the mechanisms that underlie left-right asymmetries in brain structure and function. Using a transcriptome screening approach, we found asymmetric gene expression patterns in the right when compared with the left hippocampal formation at postnatal days (P) 6, 9, and 60 in the rat. Of those genes that were differentially expressed, most were predominantly expressed in the right hippocampus at P6, whereas most were predominantly expressed in the left at P9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…and M.E.H., unpublished). However, some recent reports have identified L-R differences in gene expression programs in the rodent cortex (Sun et al, 2006;Sun et al, 2005) and hippocampus (Moskal et al, 2006), and in the size of white-matter fiber tracts associated with language regions of the human brain (Nucifora et al, 2005). Our study suggests that the asymmetric distribution of axon-guidance cues could be an important mechanism to establish patterns of connectivity in the developing embryonic CNS that underlie functional specialization.…”
Section: Research Article Neuropilin Asymmetry In Cns Connectionmentioning
confidence: 54%
“…and M.E.H., unpublished). However, some recent reports have identified L-R differences in gene expression programs in the rodent cortex (Sun et al, 2006;Sun et al, 2005) and hippocampus (Moskal et al, 2006), and in the size of white-matter fiber tracts associated with language regions of the human brain (Nucifora et al, 2005). Our study suggests that the asymmetric distribution of axon-guidance cues could be an important mechanism to establish patterns of connectivity in the developing embryonic CNS that underlie functional specialization.…”
Section: Research Article Neuropilin Asymmetry In Cns Connectionmentioning
confidence: 54%
“…Importantly, although smaller changes may actually demonstrate statistical significance, a 10-13% change, in our hands, is currently the limit of discrimination for qRT-PCR quantitation [41,56].…”
Section: Microarray Fabrication-mentioning
confidence: 71%
“…Notwithstanding, in-house design and fabrication allows a stringent level of quality control, exquisite sensitivity, and economy that typically constrains the number of arrays required to conduct experiments with sufficient numbers of biological samples/replicates and provide statistically acceptable sensitivity and specificity. This approach has reliably identified transcripts having as low as 10% differences in transcript expression between RNA samples observed in heterogeneous tissue sources such as neocortex and hippocampus [41,56]. In sum, our approach of highly selective yet broad ontological coverage of the rat transcriptome facilitates the generation of high quality data from systems/paradigms sensitive to small regulatory changes that can be confirmed by independent measurements.…”
Section: Introductionmentioning
confidence: 84%
“…Given that other studies have found reduced left hippocampal and amygdale, but not right, volumes associated with other pathological processes (e.g., Chen et al, 2004;Saylam et al, 2006), there may be neurotoxic or pre-existing developmental trajectory differences between the hemispheres that account for these differences. For example, left versus right hippocampi may differ in drug effects due to gene expression or neurotransmitter receptor discrepancies (e.g., Mostal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%